Peroxiredoxins as biomarkers of oxidative stress - Poynton, Rebecca A.; Hampton, Mark B. (Biochimica et biophysica acta, 2014)
Peroxiredoxins (Prxs) are a class of abundant thiol peroxidases that degrade hydroperoxides to water. Prxs are sensitive to oxidation, and it is hypothesized that they also act as redox sensors. The accumulation of oxidized Prxs may indicate disruption of cellular redox homeostasis. This review discusses the biochemical properties of the Prxs that make them suitable as endogenous biomarkers of oxidative stress, and describes the methodology available for measuring Prx oxidation in biological systems. Two Prx oxidation products accumulate in cells under increased oxidative stress: an intermolecular disulfide and a hyperoxidized form. Methodologies are available for measuring both of these redox states, and oxidation has been reported in cells and tissues under oxidative stress from external or internal sources. Monitoring the oxidation state of Prxs provides insight into disturbances of cellular redox homeostasis, and complements the use of exogenous probes of oxidative stress. This article is part of a Special Issue entitled Current methods to study reactive oxygen species - pros and cons and biophysics of membrane proteins. Guest Editor: Christine Winterbourn. •Peroxiredoxins are endogenous antioxidants and redox sensors.•Various biochemical properties of the peroxiredoxins make them suitable as markers of oxidative stress.•Different methods are available to detect peroxiredoxin oxidation.•Oxidized peroxiredoxins have been detected in experimental and clinical samples.